The problem of foreign policy - Murray, Gilbert, 1866-1957, author.
1 online resource
Keywords: First published in 1921, Gilbert Murray's treatise considers a largely euro-centric foreign policy during the inter-war period. Believing passionately in the prospect of a Liberal England and the hope promised by the League of Nations, with Britain at its centre, Murray argues that a secure future can only be obtained through 'equal law, good government and good faith'. Concentrating on a number of country-based studies, the main focus is on how to avoid the causes of international war; Murray supports the International Financial Commission's recommendation that this could be partly achieve.